Nonspecific therapy for Eisenmenger syndrome - A. A. Shmalts; I. E. Chernogrivov (Евразийский Кардиологический Журнал)
Eisenmenger syndrome (ES) is systemic pulmonary hypertension with venoarterial or bidirectional shunting of blood between the ventricles, atria or great arteries due to the progression of pulmonary vascular disease in the natural course of “simple” and “complex” congenital heart defects.Patients with ES require constant attention from a multidisciplinary team of specialists. One of the main tasks is not to destabilize the fragile pathological physiology, which relies on the balance of pulmonary and peripheral vascular resistance. Surgical interventions with anesthesia, if they cannot be avoided, should be performed in specialized centers. Pregnancy is contraindicated in patients with ES. Clinical symptoms of blood hyperviscosity in ES are rare.The anachronistic practice of venesections, which leads to a decrease in the oxygen transport function of the blood, iron deficiency and an increased risk of cerebrovascular complications, should be avoided. Oral and intravenous replenishment of iron deficiency improves exercise tolerance and quality of life. Routine administration of anticoagulants for ES is not indicated. In most cases, endovascular embolization of pathological collateral arteries can eliminate hemoptysis. The use of venous access requires careful prevention of embolism. Therapeutic tactics for ES are discussed in detail in this review